Keeping house : - Peterson, Margaret Kim (Jossey-Bass, 2007)
Keeping House is a wide-ranging and witty exploration of the spiritual gifts that are gained when we take the time to care for hearth and home. With a fresh perspective, mother, wife, and teacher Margaret Kim Peterson examines the activities and attitudes of keeping house and making a home. Debunking the commonly held notion that keeping house is a waste of time or at best a hobby, Peterson uncovers the broader cultural and theological factors that make housekeeping an interesting and worthwhile discipline. She reveals how the seemingly ordinary tasks of folding laundry, buying groceries, cooking, making beds, and offering hospitality can be seen as spiritual practices that embody and express concrete and positive ways of living out Christian faith in relationship to others at home, in the church and in the world.